The Development of the Web-Based Claim System in Higher Academic Institution - Herry Mohd Nasir, Mohd; Hassan, Haslinda; Ahmi, Aidi (International Journal of Engineering and Technology, 2026)
This study focuses on the development of the web-based claim system, which had previously been implemented manually. The development of this system is motivated due to the fact that the manual claim process is tedious and it is difficult for the decision maker to trace prior claims made by the respective individual. Hence, there is a slim chance to control the budget allocated for the specific activity or individual. To overcome these deficiencies, a web-based claim system is seen as an appropriate solution. Assisted by the System Development Life Cycle (SDLC) methodology, this system is developed using the ASP.Net and SQL Server to cater the recording and reporting of the claim process. The system, known as e-claim, aims to provide a platform for user in higher academic institution to process their claim automatically and to assist management in making timely and accurate decision. This paper will discuss in detail the development of the system from the requirement gathering until the design phase.
Keywords: Web-based system; decision support system; e-claim